2018
DOI: 10.1186/s12957-018-1429-z
|View full text |Cite
|
Sign up to set email alerts
|

Cancer prevalence in Pakistan: meta-analysis of various published studies to determine variation in cancer figures resulting from marked population heterogeneity in different parts of the country

Abstract: BackgroundPakistan’s population is ethnically diverse with distinct ethnic groups inhabiting various parts of the country. Cancer statistics obtained from specific regions populated by distinct ethnic groups may vary considerably. There is no national cancer registry. To determine whether there are indeed significant statistical differences in cancer incidence and prevalence, data was recorded from different parts of Pakistan based on the ethnic composition of the population in those parts.MethodsTen papers (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 8 publications
2
69
0
Order By: Relevance
“…Gender (newborn) association with RTL pointed out 29 bp longer telomeres in newborn girls compared to newborn boys. This evidence was supported by many studies which confirmed longer telomeres in girls (0.181 kb, 6.83%, 50-100 bp) [49,60,61]. An unexpected 26 bp shorter telomere was observed in low SES newborn girls, whereas girls belonging to upper middle SES had 308 bp longer telomeres.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Gender (newborn) association with RTL pointed out 29 bp longer telomeres in newborn girls compared to newborn boys. This evidence was supported by many studies which confirmed longer telomeres in girls (0.181 kb, 6.83%, 50-100 bp) [49,60,61]. An unexpected 26 bp shorter telomere was observed in low SES newborn girls, whereas girls belonging to upper middle SES had 308 bp longer telomeres.…”
Section: Discussionsupporting
confidence: 62%
“…A study found a strong relation of ethnicity (Urdu speaking and Pathan) with oral cancer having an incidence of 19 % among the Pakistani population. In this study, a high prevalence of Pathan and Urdu speaking ethnicity with shorter telomere length may be at high risk of oral cancer [61].…”
Section: Discussionmentioning
confidence: 76%
“…20 Due to the lack of data regarding its epidemiology and inadequate records at regional cancer registries and other institutions, there is no clear picture of the actual disease burden in Pakistan. 21 Most women are diagnosed at advanced stages of cervical cancer because of several factors, including a lack of knowledge and inadequate screening facilities. The cure rate is relatively low compared with developed countries in which the availability and accessibility to early detection reduce the rate of mortalities.…”
Section: Introductionmentioning
confidence: 99%
“…While the Urdu speaking ethnic community has heterogeneous Indian ancestry [56]. Thus the genetic variations exhibit significant differences in the risk of developing various disorders and disease progression in the Pakistani population [15,57,58].. Majority of the preeclamptic patients in our study were Sindhi (56%) and Urdu (27.2%) speaking.…”
Section: Discussionmentioning
confidence: 87%